Optimization of steel fibre reinforced concrete as concrete topping in composite slab construction - Noor Nabilah, Sarbini (2014)
Steel fibre can act as an alternative to replace the conventional prefabricated welded wire mesh (PWWM). It serves as a secondary reinforcement in concrete topping of the precast composite slab construction. Hence, an in-depth study on the performance was conducted to prove the notion. The study was essential due to the differences of behaviours between steel fibre in the compression and the flexural zone of the composite slab. In fact, there was no sufficient knowledge of compression mechanism of steel fibre reinforced concrete (SFRC) due to the lack of study in this area. The main objectives of this study were to investigate the structural performance of composite slab where SFRC was applied in the concrete topping and to develop an analytical model to predict the shear strength of the composite slab by validating the model with the experimental results. Aspect ratio and volume fraction were emphasised in selecting the most suitable type of steel fibre in this study. The experimental results showed that SFRC concrete topping improved the ultimate load and failure mechanism. The results also suggested that the ideal types of steel fibre to be applied in the concrete topping are SF60 and SF33 with optimum volume fraction between 0.75% and 1.00%. Furthermore, it was proven that the SFRC concrete topping has improved the shear capacity of the composite slab by 17%. The performance of the proposed analytical model in predicting the ultimate shear capacity of the composite slab with SFRC concrete topping was considered good due to its strong correlation with the experimental data. This suggested that steel fibre was suitable to replace PWWM as secondary reinforcement in concrete topping in precast composite slab construction. The proposed analytical model can also be used to predict the shear capacity of the composite slab with SFRC concrete topping.